Hydrocortisone Compared with Placebo in Patients with Septic Shock Satisfying the Sepsis-3 Diagnostic Criteria and APROCCHSS Study Inclusion Criteria: A Post Hoc Analysis of the ADRENAL Trial. (December 2019) - Venkatesh, Balasubramanian; Finfer, Simon; Cohen, Jeremy; Rajbhandari, Dorrilyn; Arabi, Yaseen; Bellomo, Rinaldo; Billot, Laurent; Glass, Parisa; Joyce, Christopher; Li, Qiang; McArthur, Colin; Perner, Anders; et al.
Abstract : Background: Two recent randomized controlled trials (Adjunctive Glucocorticoid Therapy in Patients with Septic Shock [ADRENAL] and Activated Protein C and Corticosteroids for Human Septic Shock [APROCCHSS]) of corticosteroids in patients with septic shock reported different treatment effects on 90-day mortality. Both trials enrolled patients who met the criteria for septic shock using the second international consensus definitions for sepsis and septic shock (Sepsis-2), but the APROCCHSS trial mandated a greater severity of shock as an inclusion criterion. Methods: The authors conducted post hoc sensitivity analyses of the ADRENAL trial to determine the effects of hydrocortisone versus placebo in subgroups selected using third international consensus definitions for sepsis and septic shock (Sepsis-3) diagnostic criteria or APROCCHSS inclusion criteria. Results: There were 1, 950 subjects (973 hydrocortisone and 977 placebo) who met the Sepsis-3 criteria (ADRENAL–Sepsis-3 cohort) and 905 patients (455 hydrocortisone and 450 placebo) who met the APROCCHSS criteria (ADRENAL–APROCCHSS cohort). At 90 days after randomization, in the ADRENAL–Sepsis-3 cohort, 312 of 963 (32.4%) and 337 of 958 (35.2%) patients assigned to hydrocortisone and placebo, respectively, had died (odds ratio, 0.86; 95% CI, 0.70 to 1.06; P = 0.166). The corresponding figures for the ADRENAL–APROCCHSS cohorts were 187 of 453 (41.3%) and 200 of 445 (44.9%), respectively (odds ratio, 0.84; 95% CI, 0.60 to 1.17; P = 0.303). There was no statistically significant difference in the time to death between the groups during the 90 days after randomization (hazard ratio = 0.87; 95% CI, 0.75 to 1.02; P = 0.082 for ADRENAL–Sepsis-3; and hazard ratio = 0.86; 95% CI, 0.71 to 1.06; P = 0.156 for ADRENAL–APROCCHSS cohorts). In both cohorts, patients assigned to hydrocortisone had faster resolution of shock. In the ADRENAL–Sepsis-3 cohort, patients assigned to hydrocortisone had an increase in the number of days alive and free of mechanical ventilation (57.0 ± 37.2 vs. 53.7 ± 38.2 days; 95% CI, 0.40 to 7.04; P = 0.028) and the number of days alive and free of the intensive care unit (54.3 ± 36.0 vs. 51.0 ± 37.1; 95% CI, 0.82 to 7.24; P = 0.014). Conclusions: In a post hoc analysis of the ADRENAL trial participants who fulfilled either the Sepsis-3 or the APROCCHSS inclusion criteria, a continuous infusion of hydrocortisone did not result in a lower 90-day mortality than placebo in septic shock. Abstract : In a post hoc analysis of the Adjunctive Glucocorticoid Therapy in Patients with Septic Shock (ADRENAL) trial, in participants who fulfilled either the Sepsis-3 or -2 inclusion criteria or those with severe septic shock, a continuous infusion of hydrocortisone did not result in a lower 90-day mortality than placebo.Supplemental Digital Content is available in the text.